2018
DOI: 10.1016/j.snb.2017.10.149
|View full text |Cite
|
Sign up to set email alerts
|

SnO2-MOF-Fabry-Perot optical sensor for relative humidity measurements

Abstract: In this paper, a new optical fiber sensor for relative humidity measurements is presented and characterized. The sensor is based on a SnO2 sputtering deposition on a microstructured optical fiber (MOF) low-finesse Fabry-Pérot (FP) sensing head. The feasibility of the device as a breathing sensor is also experimentally demonstrated. The interrogation of the sensing head is carried out by monitoring the Fast Fourier Transform phase variations of the FP interference frequency. This method substitutes the necessit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In this work, the deposition time of each sensor has been selected in order to enable simultaneous measurement in the same atmosphere avoiding crosstalk between sensors. For this reason, their sensitivity is not maximal when compared with the results showed in [46], [55], [56], as they were optimized.…”
Section: Portsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this work, the deposition time of each sensor has been selected in order to enable simultaneous measurement in the same atmosphere avoiding crosstalk between sensors. For this reason, their sensitivity is not maximal when compared with the results showed in [46], [55], [56], as they were optimized.…”
Section: Portsmentioning
confidence: 98%
“…Relative humidity sensors were developed by creating a thin film of SnO2 inside the holes of the MOF fiber through the sputtering process, as authors previously demonstrated in [55]. VOCs presence sensors were developed with the same technique but changing the sensing material to ITO [56].…”
Section: Portsmentioning
confidence: 99%
“…Microstructured optical fibers (MOFs) present great sensing potential and they have shown improved properties over traditional optical fiber sensors overcoming some of their handicaps [14][15][16]. For example, several pure silica suspended-core fibers have been used in temperature and curvature sensing [17], gas sensing [18], or relative humidity (RH) sensing [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, an optical fiber sensor based on a sputtering deposition on a MOF is presented for real moisture measurements and compared simultaneously with a commercial capacitive sensor. The operation principle of the humidity optical sensor has been previously reported by authors [19] showing in detail the construction process of an optimized sensing head and its performance towards humidity variations. In the present paper, the authors propose, for the first time, a sensor that has been adapted and used for measurements in real soil conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation